CHARACTERISTICS OF CATFISH (Pangasius pangasius) VISCERA OIL PURIFIED WITH BENTONITE (Jurnal Teknologi Pangan, 2022)
The fishing industry is a very broadline business with various processes that have by-products. Catfish viscera which includes digestive tract, liver, bile, and stored fat (belly fat) is a potential source of fat to be processed into fish oil with high content of unsaturated fatty acids, especially omega 3. This study aims to determine the effect of adding bentonite to the purification process of catfish oil from viscera on the characteristics of pure fish oil. This study used a completely randomized design (CRD) consisting 4 treatments of bentonite percentage, 0%, 4%, 7% and 10%. Parameters measured were free fatty acid, acid number, peroxide number, paraanisidin number (p-anisidin), total oxidation, and yield. Data analysis used Analysis of Variance (ANOVA) and continued with Duncan's Multiple Distance Test. The results of this study indicate that the addition of bentonite to pure fish oil has a significant effect on the characteristics of fish oil from each treatment. The best purification was found in the addition of 10% bentonite that having the characteristics of 0.62% free fatty acids, 0.12 mgKOH/g acid number, 0 meq/kg peroxide number (not detected), paraanisidin number 1.60 meq/kg, total oxidation 1.60 meq/kg, and yield of 75.23 ± 0.194%. DOI : https://doi.org/10.33005/jtp.v16i2.3226